РАЗРАБОТКА КОНСТРУКЦИИ ПИЛЬЧАТОЙ СЕКЦИИ ХЛОПКООЧИСТИТЕЛЬНОГО АГРЕГАТА (Scientific journal of the Fergana State University, 2023)
The article presents a new design of the serrate section of a cotton-cleaning unit with transporting brush drums having different diameters and grate on elastic supports with a certain thickness; the design features of the working parts of the serrate section of the cotton-cleaning unit are considered in detail, as well as the principle of its’ operation. The results of testing the serrate section are given, along which the ways to improve the cleaning effect of raw cotton from coarse litter are identified.